Parametric estimates of the kinetic energy in the atmospheric boundary layer from minisodar measurements - Simakhin, Valerii A.; Potekaev, Aleksandr I. 1951-; Cherepanov, Oleg S.; Shamanaeva, Luidmila G. (Proceedings of SPIE)
In the present work, the kinetic energy of wind outliers taken to mean wind velocity values exceeding a preset value and including wind gusts are compared with the mean wind kinetic energy component retrieved from minisodar measurements using the robust parametric algorithm proposed by the authors. Allowance for the contribution of the wind outliers in the parametric estimates of the wind kinetic energy enables its fine structure to be determined and its effect on light flying objects, high-rise buildings, bridges to be estimated and the energy potentials of wind turbines to be evaluated.